Machine-made sand concrete containing mountain flour and corresponding mix proportion design method

By using stone powder from manufactured sand as a cementing material to replace part of the cement and fly ash, a new cementing system is formed, which solves the problem of the cementing activity of stone powder in concrete that has been neglected. This achieves efficient resource utilization and strength assurance, and improves the performance and environmental friendliness of concrete.

CN120878004AActive Publication Date: 2025-10-31中建三局集团西北有限公司 +2

Patent Information

Application Number
CN202511386744.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-10-31
Estimated Expiration
2045-09-26

AI Technical Summary

Technical Problem

In existing technologies, stone powder in manufactured sand is regarded as an inert mineral admixture or useless waste, which leads to unreasonable concrete gradation, increased cement usage, non-low carbon concrete, poor volume stability, and serious waste of resources.

Method used

Stone powder in manufactured sand is used as part of the cementitious material. Its content is determined by sieving, and 10%-20% of it replaces cement. The remaining part replaces fly ash and mineral powder to form a new cementitious system. The strength of the mortar is calculated using the strength influence coefficient γLf=-3.16x²-0.048x+1. The water content is adjusted to meet the strength requirements of the mixture.

Benefits of technology

It has achieved efficient resource utilization of manufactured sand with high stone powder content, reduced cement usage, ensured the workability, strength and durability of concrete, and achieved a 28-day compressive strength of more than 80% of the benchmark concrete, thus expanding the application scenarios of manufactured sand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120878004A_ABST
    Figure CN120878004A_ABST
Patent Text Reader

Abstract

The invention relates to the field of concrete design, and particularly discloses stone powder-containing machine-made sand concrete and a corresponding mix proportion design method. The method comprises the steps that the use amount of coarse aggregate, fine aggregate and a cementing material of concrete is calculated, the fine aggregate stone powder-containing machine-made sand is subjected to rapid screening, the stone powder content of the fine aggregate stone powder-containing machine-made sand is measured, all the stone powder-containing machine-made sand is counted into the cementing material, part of cement, fly ash and mineral powder are replaced, a cementing system is formed, 10%-20% of the cement is replaced with the cement, and the remaining part of the cement is replaced with the fly ash and the mineral powder; calculating a strength influence coefficient under the specific cement replacement ratio of the stone powder by adopting a formula gamma Lf =-3.16 x-0. 048 x + 1, and calculating the mortar strength of the gelling system according to the strength influence coefficient; and adjusting and determining the water consumption meeting the preparation strength requirement, and finally determining the dosage of each component of the concrete. The stone powder in the powder-containing machine-made sand serves as a gelling component, efficient resource utilization of the machine-made sand with the high stone powder content is achieved, the use amount of cement and coal ash is reduced, and the problem that concrete is not low in carbon for a long time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of concrete, and more specifically, to a concrete containing stone powder manufactured sand and a corresponding mix design method. Background Technology

[0002] In recent years, manufactured sand has become the main source of sand for concrete. The production process of manufactured sand will bring a certain amount of stone powder. When using the traditional mix design method, the stone powder in manufactured sand is included as part of the fine aggregate, which leads to the calculated sand ratio being greater than the actual sand ratio. The gradation of each component of the concrete is unreasonable. In order to meet the workability requirements of concrete, the total amount of cement or cementitious materials is usually increased to improve the situation. This results in a larger amount of cement or cementitious materials used in the concrete, which is not conducive to low carbon and environmental protection, nor is it conducive to the volume stability of concrete, resulting in the cracking problem remaining serious.

[0003] Manufactured sand, as an important building aggregate, is rock particles with a particle size of less than 4.75 mm produced through mechanical crushing, screening, and shaping of parent rock. During production, a large amount of stone powder (usually referring to particles with a particle size of less than 75 μm) is inevitably generated. Especially under dry production processes, the stone powder content in manufactured sand often exceeds 10%, and can even reach over 20%. The current standard, "Standard for Quality and Testing Methods of Sand and Stone for Ordinary Concrete" (JGJ52), strictly stipulates that the stone powder content of manufactured sand used for C25 and below strength grade concrete shall not exceed 10%; and for C30-C55 strength grade concrete, the stone powder content shall not exceed 7%. These regulations consider the stone powder in manufactured sand as fine aggregate. The technical background of this patent is how to resolve the contradiction between existing regulations and the high stone powder content of manufactured sand, and how to scientifically design and produce concrete mix proportions according to existing technical specifications, thereby achieving the rational utilization of powder-containing manufactured sand.

[0004] Currently, the industry's common methods for treating stone powder in manufactured sand have fundamental flaws, mainly in the following two aspects: One common misconception is classifying limestone powder as an "inert mineral admixture." According to standards such as the "Technical Specification for the Application of Limestone Powder in Concrete" (JGJ / T 318), limestone powder meeting the activity index standard is often considered an inert mineral admixture. This method ignores the potential chemical cementitious activity of limestone powder and fails to calculate its contribution to the cementitious material system. Limestone powder, which should be included in the cementitious material system, is instead counted as other components, resulting in a calculated sand ratio higher than the actual sand ratio. This leads to an unreasonable gradation of the concrete components and a calculated water-cement ratio higher than the actual water-cement ratio, reducing the workability of the concrete. To meet workability requirements while maintaining strength, it is necessary to increase the water content (actually, the paste at a certain water-cement ratio), leading to increased cement or cementitious material usage. This results in concrete that is not low in carbon, an increased paste-aggregate ratio, poor volume stability, and a tendency to crack, leading to severely insufficient durability.

[0005] Secondly, some manufacturers forcibly wash away stone powder as "useless waste": A more conservative and common practice is to invest additional costs, water, and energy to wash manufactured sand in order to meet the upper limit requirements for stone powder content in current standards, discharging the valuable stone powder as "sludge." This not only causes significant waste of resources but also brings serious environmental burdens (such as sludge accumulation and water pollution) and economic costs (treatment costs and sand loss).

[0006] Therefore, developing a method that can scientifically measure the cementitious properties of stone powder and guide the precise design and production of manufactured sand concrete with high stone powder content has become an urgent need to promote the resource utilization and technological development of the industry. Summary of the Invention

[0007] To address the aforementioned issues, this application provides a method for designing the mix proportion of manufactured sand concrete containing stone powder.

[0008] The design concept of this application is as follows: The method of this application includes: calculating the amount of coarse and fine aggregates and cementitious materials in concrete; using a rapid sieving method to determine the stone powder content of the fine aggregate (manufactured sand containing stone powder) and including it entirely in the cementitious materials, replacing part of the cement, fly ash, and mineral powder to form a new cementitious system, wherein 10%-20% of the cement content is replaced, and the remaining part replaces fly ash and mineral powder; using formula γ Lf =-3.16x²-0.048x+1 calculates the strength influence coefficient under the specific proportion of stone powder replacing cement, and calculates the mortar strength of the cementitious system accordingly; adjusts and determines the amount of water to meet the strength requirements of the mix design, and finally determines the amount of each component of the concrete.

[0009] The technical solution adopted in this application is as follows: In a first aspect, this application provides a method for designing the mix proportion of manufactured sand concrete containing stone powder, comprising: (1) According to the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ55, the total mass of coarse and fine aggregates and the amount of cementitious materials in the reference concrete are calculated and determined by the absolute volume method, and the amount of cement, fly ash and mineral powder in the cementitious materials are determined respectively. (2) Using manufactured sand containing stone powder as fine aggregate, the stone powder content in the fine aggregate is determined by sieving, and stone powder is used to replace part of the cement and / or fly ash and mineral powder in the mix proportion calculation to form a cementitious system composed of cement, fly ash, mineral powder and stone powder in a specific proportion. The principles for stone powder substitution are as follows: Stone powder in manufactured sand can replace 10%-20% of the cement content; If there is any stone powder left over, the remaining stone powder will be used to replace fly ash and mineral powder. (3) Calculate the mortar strength of the novel cementitious system based on the strength influence coefficients of each component material, wherein the strength influence coefficient γ of the stone powder replacing cement is... Lf Calculate using the following formula: γ Lf = -3.16x 2 - 0.048x + 1 Equation (I) In the formula, x is the mass percentage (%) of stone powder replacing cement; (4) Calculate the required water-cement ratio based on the concrete mix strength: If the water-cement ratio meets the strength requirements, determine the corresponding water consumption; if not, readjust the amount of cementitious material and iterate until the water-cement ratio meets the strength requirements. (5) Finally determine the amount of each component in the unit volume of concrete.

[0010] Furthermore, the aforementioned manufactured sand containing stone powder originates from common diabase, basalt, dolomite, and limestone.

[0011] Furthermore, in step (2) above, when stone powder replaces cement in different proportions, the ratio of the strength of the resulting concrete to the strength of the reference concrete conforms to the following rule: When the proportion of stone powder replacing cement is 10% of the theoretical cement content, the strength ratio of the resulting concrete to the reference concrete strength is 89.0%-98.0%. When the proportion of stone powder replacing cement is 15% of the theoretical cement content, the strength of the resulting concrete is 84.5%-96.4% of the strength of the reference concrete. When the proportion of stone powder replacing cement is 20% of the theoretical cement content, the strength of the resulting concrete is 80.88%-89.82% of the strength of the reference concrete.

[0012] Furthermore, in step (3) above, in order to further incorporate the influence of stone powder particle size and chemical composition on concrete strength into the calculation system, the strength influence coefficient γ is calculated according to the formula. Lf Based on this, the range of values ​​for the strength influence coefficient corresponding to the 95% confidence interval of the stone powder replacement ratio is also introduced.

[0013] Furthermore, in step (3) above: When the stone powder replacement ratio is 10% of the theoretical cement content, the strength influence coefficient γ Lf The 95% confidence interval is 0.912–0.979; When the stone powder replacement ratio is 15% of the theoretical cement content, the strength influence coefficient γ Lf The 95% confidence interval is 0.848–0.964; When the stone powder replacement ratio is 20% of the theoretical cement content, the strength influence coefficient γ Lf The 95% confidence interval is 0.805-0.866.

[0014] Furthermore, the above describes the determination of the intensity influence coefficient γ. Lf When determining the specific value, the following steps are also included: The stone powder was subjected to negative pressure sieving to determine the proportion of sieve residue of particles larger than 45μm. If the percentage of the sieve residue is less than 10%, then the upper limit of the corresponding confidence interval is taken as γ. Lf ; If the percentage of the sieve residue is 10%-20%, then the value calculated according to formula (I) is taken as γ. Lf ; If the percentage of the sieve residue is greater than 20%, then the lower limit of the corresponding confidence interval is taken as γ. Lf .

[0015] Furthermore, in step (2) above, the strength influence coefficient of the stone powder used to replace fly ash and mineral powder in equal amounts is adopted from the strength influence coefficient of the replaced fly ash and mineral powder, and the value of the strength influence coefficient is determined in accordance with the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ 55.

[0016] Secondly, this application provides a stone powder-containing manufactured sand concrete prepared according to the above-mentioned mix design method, which includes the following components: Cement, fly ash, mineral powder, water; Coarse aggregate, manufactured sand and fine aggregate containing stone powder; In this process, the stone powder in the manufactured sand serves as part of the cementitious material, and together with cement, fly ash, and mineral powder, it forms a composite cementitious system.

[0017] Furthermore, the aforementioned stone powder originates from powder with a particle size of less than 75μm produced during the production of manufactured sand from common diabase, basalt, dolomite, or limestone.

[0018] Furthermore, the 28-day compressive strength of the above-mentioned concrete is not less than 80% of the strength of the benchmark concrete without stone powder under the same conditions.

[0019] In summary, this application has the following beneficial effects: This application, for the first time, uses systematic materials science analysis (laser particle size analyzer, XRD, mortar test, mercury porosimetry) to confirm that different types of rock-based manufactured sand and gravel powder are not "inert materials," but rather possess distinct cementitious material properties. Based on this, this application breaks through the traditional understanding that current standards simply classify them as "inert admixtures" or "waste materials," and establishes a new theory and method for incorporating stone powder as an independent cementitious component into mix design.

[0020] This invention uses stone powder in manufactured sand containing powder as a cementing component and provides a mix proportion calculation process and control parameters, thus achieving scientific and precise mix proportion design. - A clear rule for stone powder substitution was established (prioritizing the substitution of 10%~20% of cement, with the remainder replacing fly ash and / or mineral powder), and the influence coefficient of excess stone powder was innovatively linked to the materials being substituted (cement, fly ash, mineral powder), solving the core technical problem that high-stone-powder-content manufactured sand cannot be used in the preparation of high-performance concrete. - A quantitative design method based on the intensity influence coefficient is proposed, using the formula γ Lf = -3.16x² - 0.048x+ 1 and the corresponding 95% confidence interval can accurately quantify the contribution of fossil powder to concrete strength; - An principle for determining the strength influence coefficient based on stone powder particle size (45μm sieve residue) was introduced, making the design results more reliable and more in line with reality.

[0021] This application achieves efficient resource utilization of manufactured sand with high stone powder content, reduces the amount of cement and fly ash used, and solves the long-term problem of non-low carbon emissions in concrete. The workability, strength, and durability of the prepared concrete can be effectively controlled and guaranteed through precise design, and the 28-day compressive strength can reach more than 80% of the benchmark concrete, with stable and reliable performance. It breaks through the current standard restrictions on stone powder content, enabling manufactured sand with high stone powder content to be safely used in concrete projects with strength grades of C30 and above, greatly expanding the resource range and application scenarios of high-quality manufactured sand. Attached Figure Description

[0022] Figure 1 This is a field photo of the concrete shrinkage test in Experiment Example 1.

[0023] Figure 2 This is a field photo of the concrete slab cracking test in Experiment Example 1.

[0024] Figure 3 This is a diagram showing the cracking test of a concrete slab in Experiment Example 1.

[0025] Figure 4 This is a diagram showing the 7-day shrinkage of concrete in Experiment Example 1.

[0026] Figure 5 The following is an analysis of the particle size of stone powder from different rock types in Experiment Example 2: A is the differential distribution curve, and B is the integral distribution curve.

[0027] Figure 6 XRD analysis of different rock powder mineral components in Experiment Example 2: A is the XRD pattern of CA (diabase), HC-S1 (dolomite), HC-S2 (limestone), and QH (limestone); B is the XRD pattern of LT-S1 (basalt), LT-S2 (dolomite), LT-S3 (limestone), and SY (limestone).

[0028] Figure 7 The following is a graph showing the mortar strength analysis for eight different stone powder substitution ratios in Experiment Example 3: A represents the 3-day mortar strength; B represents the 7-day mortar strength; and C represents the 28-day mortar strength.

[0029] Figure 8 The pore size distribution curves for the eight stone powders with different replacement ratios in Experiment Example 3 are shown: A is for a 10% cement replacement ratio; B is for a 20% cement replacement ratio; and C is for a 30% cement replacement ratio.

[0030] Figure 9 The porosity of the cement-based material under different substitution ratios in Experiment Example 3 is given.

[0031] Figure 10 The normal distribution diagrams for different stone powder substitution ratios in Experiment Example 4 are as follows: A represents a 10% cement substitution ratio; B represents a 15% cement substitution ratio; and C represents a 20% cement substitution ratio.

[0032] Figure 11 The curve showing the influence coefficient of concrete strength in Experiment Example 4.

[0033] Figure 12 The curve of the influence coefficient of concrete strength in Experiment Example 4 (95% confidence interval). Detailed Implementation

[0034] The embodiments of the present invention will be described in detail below with reference to the examples. However, those skilled in the art will understand that the following examples are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Specific conditions not specified in the examples shall be carried out according to conventional conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0035] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0036] Example

[0037] This embodiment provides a mix design method for manufactured sand concrete containing stone powder, the objective of which is to prepare C50 concrete. The mix design method includes: (1) According to the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ55, the total mass of coarse and fine aggregates and the amount of cementitious materials in the reference concrete are calculated and determined by the absolute volume method. The amounts of cement, fly ash and mineral powder in the cementitious materials are also determined separately, as shown in Table 1. Table 1. Theoretical Calculations of Each Component of C50 Concrete (Unit: kg / m³) 3 )

[0038] (2) Select manufactured sand containing stone powder (derived from diabase) as fine aggregate, perform rapid screening, and determine the fine aggregate content (710 kg / m³). 3 The stone powder content in the sample is 60.9 kg / m³. 3 The stone powder was sieved using a negative pressure sieve method, and the mass percentage of particles larger than 45μm was 11.3%.

[0039] (3) Stone powder was used as part of the gelling material, replacing cement, fly ash and mineral powder at 10%, 20% and 11% respectively. At the same time, the total amount of fine aggregate was slightly adjusted. The results are shown in Table 2: Table 2. Dosage of each component in C50 concrete after substitution (unit: kg / m³) 3 )

[0040] Based on the strength influence coefficients of each component material, the mortar strength of the cementitious system is calculated, where: - Strength influence coefficient γ of stone powder as a substitute for cement Lf Calculate using the following formula: γ Lf = -3.16x 2- 0.048x + 1 = 0.9636 To reduce the impact of stone powder particle size and chemical composition on concrete strength, when the stone powder replacement ratio is 10% of the theoretical cement content, the strength influence coefficient γ is [value missing]. Lf The 95% confidence interval is 0.912–0.979; since the sieve residue of particles larger than 45 μm accounts for 11.3% after negative pressure sieving of stone powder, the calculated value of 0.9636 is taken as the final γ. Lf ; - The strength influence coefficient of stone powder replacing fly ash shall be determined in accordance with the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ55; - The strength influence coefficient of stone powder replacing mineral powder shall be determined in accordance with the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ55.

[0041] (5) Calculate the water-cement ratio based on the concrete mix design strength, determine the corresponding water usage, and finally determine the usage of each component per unit volume of concrete, as shown in Table 3. The concrete prepared according to this mix design is designated as YH-C50.

[0042] Table 3. Mix design of each component of C50 concrete (unit: kg / m³) 3 )

[0043] This comparative example provides a mix design route for preparing C50 concrete according to the traditional method, which takes stone powder in stone powder manufactured sand as part of the fine aggregate. The specific mix design is shown in Table 4, numbered JZ-C50.

[0044] Experimental Example 1 Performance tests were conducted on the C50 concrete provided in the examples and comparative examples.

[0045] 1. Component Comparison Analysis: Table 4. Comparative Analysis of C50 Concrete Mix Design (Unit: kg / m³) 3 )

[0046] According to the method of Example 1 of this application, all stone powder should be included in the water-cement ratio calculation, the amount of cement in a single cubic meter of concrete is reduced by 30 kg, the total amount of cementitious materials is reduced by 60 kg, and the paste-aggregate ratio is reduced from the original 0.58 to 0.49.

[0047] 2. Experimental Methods: - The NELD-ES731 series non-contact concrete shrinkage deformation tester was used to conduct early autogenous shrinkage tests on concrete, such as... Figure 1 As shown; - Concrete slab restraint cracking test was conducted according to the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB / T50082), such as... Figure 2 As shown.

[0048] 3. Experimental Results (1) The compressive strength values ​​at different ages are shown in Table 5.

[0049] Table 5. Compressive strength values ​​(MPa) of C50 concrete mix design

[0050] The surface cracking of slabs in two concrete groups, JZ-C50 and YH-C50, was monitored at 3 days. The results are as follows: Figure 3 As shown, two cracks were found on the surface of the JZ group plate, with the widest crack reaching 0.2 mm. No cracks visible to the naked eye were found on the surface of the YH group.

[0051] (2) The results of the concrete shrinkage test are as follows Figure 4 As shown.

[0052] Depend on Figure 4 It can be seen that the shrinkage curves of both JZ-C50 and YH-C50 show a trend of slight expansion followed by shrinkage. Moreover, the shrinkage value increases rapidly in the first 40 hours, and then gradually slows down. When the test time is 40 hours, the shrinkage value of YH-C50 accounts for about 73% of the shrinkage value of JZ-C50. The volume stability of YH-C50 concrete is significantly better than that of JZ-C50 concrete designed using the traditional technical route.

[0053] Experimental Example 2 This experiment investigated the cementitious properties of stone powder in silty manufactured sand from different rocks.

[0054] 1. Test method: (1) Experimental raw materials: Stone powder was derived from eight groups of manufactured sand commonly used in engineering, numbered CA (diabase), LT-S1 (basalt), LT-S2 (dolomite), LT-S3 (limestone), SY (limestone), QH (limestone), HC-S1 (dolomite), and HC-S2 (limestone). The manufactured sand was sieved according to the national standard "Sand for Construction" (GB / T14684-2022), and particles smaller than 0.075mm were used as stone powder for research. PO 42.5 / 42.5 ordinary Portland cement was used, fly ash was Grade II fly ash produced by Datang Shenglong Power Plant, mineral powder was S95 grade mineral powder produced by Lizhilin Company, and the sand was ISO standard sand.

[0055] (2) Experimental design The influence of stone powder as a cementitious material on concrete strength was investigated according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). A fly ash substitution test with the same proportion was conducted as a control in the experimental design. To eliminate the influence of factors other than stone powder on the pore structure of cement-based materials, mercury intrusion porosimetry (MIP) specimens were prepared using cement paste with the same water-cement ratio as the mortar. Based on the mortar strength test results and mercury intrusion porosimetry porosity analysis, a reasonable range of stone powder substitution ratios was obtained. Concrete strength tests were conducted at common water-cement ratios of 0.3 and 0.5 with different stone powder dosages, in accordance with the national standard "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081-2019).

[0056] To eliminate the influence of other factors on strength, in addition to selecting different batches of cement, the raw materials used in the test were selected with the same technical parameters for materials such as gravel, fly ash, and mineral powder. Since the cement was from different batches, the final strength index was expressed as a ratio to the baseline strength value of the control group.

[0057] (3) Mortar and concrete mix proportions For details on mortar testing and concrete mix proportions, please refer to Tables 6 and 7. Table 6. Mortar test mix proportions

[0058] Table 7. Concrete Mix Design

[0059] 2. Results and Analysis 2.1 Particle size analysis Particle size analysis was performed on eight representative groups of stone powder using a laser particle size analyzer. The particle size curves are shown below. Figure 5 As shown.

[0060] Based on the above test results, the evaluation values ​​D(n) of different particle sizes of stone powder and other cementitious materials and the cumulative proportion of different particle sizes were established, as detailed in Tables 8 and 9.

[0061] Table 8. Evaluation values ​​of different particle sizes of powder (µm)

[0062] Table 9. Cumulative percentage of different particle sizes in powder materials (%)

[0063] Based on the above analysis, different manufactured sand and gravel powders have different particle size distributions due to different production processes. However, the particle size distribution of different rock powders is between that of mineral powder and fly ash, indicating that stone powder, in terms of particle size distribution, has the property of being able to replace part of cement, fly ash and mineral powder.

[0064] According to the "central mass hypothesis" model, stone powder can serve as a secondary central mass with a particle size ≥10μm, while cement paste is the secondary medium. The cumulative distribution values ​​of all stone powder particles at 45µm are less than those of cement particles at 45µm, effectively compensating for the lack of particles between 0.075mm and 0.045mm in the current cement composition due to its excessive fineness, especially for relatively coarser stone powders such as LT-S1 and LT-S2. Therefore, from a size effect perspective, different stone powders satisfy the properties of "cementing materials," effectively filling the gap in particle size distribution of fillers below 0.075mm in concrete components, thus better improving the particle size distribution of cementing materials and optimizing the filling effect. Therefore, combining appropriate amounts of stone powder with cement, fly ash, and mineral powder to form a "stone powder-cement-mineral powder-fly ash" combined cementing material system will result in a better overall particle size distribution and superior concrete performance.

[0065] 2.2 Chemical composition of different stone powders Based on the XRD analysis results of different stone powders ( Figure 6 The main component of stone powder from different rock types is CaCO3. The chemical composition of different stone powders is shown in Table 10. Table 10. Mineral composition of different stone powders

[0066] Therefore, it can be seen that CaCO3 is the main component in common rock powder, while the contents of Ca(Mg)CO3 and SiO2 vary within a certain range. However, the main chemical components CaCO3, Ca(Mg)CO3, and SiO2 possess potential hydration activity, provided the specific surface area is greater than 350 m². 2 / kg and in the presence of alkali or sulfate, it can have a certain ability to generate calcium silicate hydrate (CSH).

[0067] 2.3 Specific surface area The test method and procedure for the specific surface area of ​​stone powder were in accordance with the standard "Cement Specific Surface Area Test Method - Blaine Method" (GB / T8074-2008), and the results are shown in Table 11.

[0068] Table 11. Specific surface area values ​​of different stone powders (m²) 2 / kg)

[0069] According to the fineness test results, the specific surface area of ​​common manufactured sand and gravel powder is close to 350m². 2 The concentration of stone powder at approximately 1 / kg provides the necessary physical conditions for activation.

[0070] In summary, analysis of the particle size distribution, chemical composition, and fineness of stone powder shows that common stone powder has similar cementitious material properties to other cementitious materials and can be used as a cementitious material to replace part of the cement.

[0071] Experimental Example 3 This experimental example examines the mortar strength and mercury intrusion porosimetry results under different proportions of stone powder substitution.

[0072] The experimental method for this example is described in Example 2.

[0073] 3.1 Mortar strength The strengths of mortar specimens at 3d, 7d, and 28d under different stone powder substitution ratios of 0%, 10%, 20%, 30%, and 40% are as follows: Figure 7 As shown.

[0074] As can be seen from the 3D strength measurement ( Figure 7 A) The average strength of the specimens with a 10% replacement ratio is about 10% to 15% higher than the baseline strength of the same age without stone powder; the average strength of the specimens with a 20% replacement ratio is slightly lower than the baseline strength of the specimens without stone powder, by about 5%; the average strength of the specimens with 30% and 40% replacement ratios is even lower than the baseline strength of the specimens without stone powder, by about 0% to 30%; the 3-day strength of the specimens with stone powder varies depending on the type of stone powder in each different dosage range. The 3-day strength of the stone powder mortar specimens with the same replacement ratio as fly ash shows a greater decrease, indicating that the contribution of stone powder to the strength of concrete at 3 days is much greater than that of fly ash.

[0075] The strength was determined by the 7-day strength test. Figure 7 (B) The average strength of concrete with a 10% replacement ratio was about 10% higher than the baseline strength of concrete without stone powder at the same age; the average strength of concrete with a 20% replacement ratio was further reduced, by about 15% to 25%; the average strength of concrete with 30% and 40% replacement ratios was even more significantly reduced than the baseline strength of concrete without stone powder, by about 25% to 45%; the strength of the stone powder-containing test blocks at 7 days varied depending on the type of stone powder within each different dosage range. The strength of the fly ash-containing test blocks at 7 days with the corresponding replacement ratio was close to the lower limit of the strength range of mortar with stone powder at the same age, indicating that the contribution of stone powder to the strength of concrete at 7 days was greater than that of fly ash.

[0076] The strength was determined by the 28-day strength test. Figure 7(C) The average strength of concrete with a 10% replacement ratio is slightly lower than the baseline strength of concrete without stone powder at the same age by about 5%; the average strength of concrete with a 20% replacement ratio is further lower than the baseline strength of concrete without stone powder by about 10% to 15%; the average strength of concrete with 30% and 40% replacement ratios is significantly lower than the baseline strength of concrete without stone powder by about 30% to 45%. The strength of the test blocks with stone powder at 28 days varies depending on the type of stone powder used. The mortar strength of fly ash at the same replacement ratio at 28 days is close to the average mortar strength of each interval with stone powder at the same age, indicating that the average contribution of different stone powders to the concrete strength at 28 days is consistent with that of fly ash.

[0077] In combination with the above Figure 5 It is evident that the particle size of stone powder is a crucial factor influencing the upper and lower limits of each strength range. Compared to cement or fly ash, stone powder has a relatively smaller particle size. At replacement ratios of 10% and 20%, its 3-day and 7-day strengths are generally within the upper limit range of each strength range. However, at replacement ratios of 30% and 40%, the 3-day and 7-day strengths are not significantly affected by particle size. At replacement ratios of 10% and 20%, particle size distribution has a significant impact on the 28-day strength of the specimens, but at replacement ratios of 30% and 40%, the 28-day strength is not significantly affected by particle size. Furthermore, for stone powders with similar fineness, chemical composition is another important factor influencing the upper and lower limits of each strength range.

[0078] 3.2 Mercury Porosimetry Analysis The pore size distribution and porosity results of 28-day slurry specimens made from fly ash, mineral powder, and different types of manufactured sand and gravel from engineering processes, at equal proportions of 0%, 10%, 20%, and 30% cement replacement, are as follows: Figure 8 As shown.

[0079] At substitution ratios of 10%, 20%, and 30% for different types of stone powder, similar to fly ash and mineral powder, the differential pore size distribution curves of the slurry specimens were all higher than those of the baseline specimens without stone powder. This indicates that the porosity of the cement-based slurry material containing stone powder increases significantly, leading to a decrease in concrete strength. Therefore, there is an upper limit to the amount of stone powder that can be added to ensure concrete quality.

[0080] Depend on Figure 9It can be seen that the average porosity of all cement pastes containing stone powder in the replacement ratios of 10%, 20%, and 30% are 19.86%, 19.89%, and 21.73%, respectively. This indicates that the average porosity at the 20%–30% replacement ratio is larger than that at the 10%–20% replacement ratio, and the porosity of each type of stone powder in the 30% replacement ratio range is also relatively large. Considering the strong correlation between concrete strength and porosity, it can be argued that a stone powder replacement ratio greater than 20% is detrimental to strength development. This aligns with the pattern that the strength of mortar specimens decreased more significantly from the baseline strength at stone powder replacement ratios of 30% and 40%.

[0081] The common sand content in concrete mix proportions is 800 kg / m³. 3 ~1000kg / m 3 The national standard "Sand for Construction" (GB / T14684-2022) stipulates that the stone powder content in manufactured sand should not exceed 15%, so the maximum stone powder content in a single cubic meter of concrete is approximately 120 kg / m³. 3 ~150kg / m 3 Considering stone powder as a cementing material, the optimal substitution ratio of stone powder in manufactured sand that simultaneously satisfies both strength and workability is approximately 8% to 22% of the cement mass.

[0082] Based on the comprehensive analysis of the strength and mechanism of mortar with different substitution ratios, stone powder in manufactured sand of various rock types commonly used in engineering can be used as a cementing material. Therefore, the stone powder content in manufactured sand should be considered when designing concrete mix proportions, and the cement dosage should be reduced by the "cement with the optimal substitution ratio". A cement substitution ratio of 10% to 20% can meet the strength, workability and other properties of concrete. If the stone powder content in manufactured sand exceeds the above range, the excess portion can be considered to replace part of the fly ash or mineral powder.

[0083] Experimental Example 4 This experiment investigates the influence coefficient of different stone powder ratios on concrete strength. 4.1 Parameter Analysis Based on nine common stone powder groups, each group was used to replace cement at a ratio of 10%, 15%, and 20% to obtain concrete strength values.

[0084] Combining mortar test strength data and concrete strength data at 10%, 15%, and 20% stone powder replacement ratios, 24 data points were used as random samples for each group at 10% and 20% replacement ratios, and 16 data points were used as random samples for each group at 15% replacement ratio. The probability density distribution diagrams for each group according to different stone powder replacement ratios are shown below. Figure 10 ).

[0085] The normal distribution of different stone powder replacement ratios has two parameters: mean and standard deviation. The mean parameter represents the average level of concrete strength under the same stone powder replacement ratio, while the standard deviation parameter represents the homogeneity of concrete strength under the same stone powder replacement ratio. The better the homogeneity, the smaller the standard deviation, and the curve exhibits a "tall and thin" distribution, meaning that all values ​​are concentrated around the mean, and the dispersion is smaller. Figure 10 It can be seen that the distribution of the histogram of the ratio of the test strength to the reference strength of stone powder under each substitution ratio is well fitted with the probability distribution curve. It can be considered that the distribution of the ratio of the test strength to the reference strength of stone powder under each substitution ratio conforms to the normal distribution curve.

[0086] 4.2 Normal Distribution Model Analysis The concrete strengths under different replacement ratios of 10%, 15%, and 20% stone powder were obtained and the normal model was verified. The corresponding average value, standard deviation, and quantile at the 95% probability were calculated based on the data, as shown in Table 12.

[0087] Table 12. Parameter values ​​of the normal distribution model

[0088] Experimental data analysis shows that when the stone powder replacement ratio is 10%, the ratio of concrete strength to the benchmark strength is 89.0%~98.0%; when the stone powder replacement ratio is 15%, the ratio of concrete strength to the benchmark strength is 84.5%~96.4%; and when the stone powder replacement ratio is 20%, the ratio of concrete strength to the benchmark strength is 80.88%~89.82%.

[0089] 4.3 Strength Influence Coefficient The strength influence coefficient of stone powder is obtained by normalizing the strength test results of concrete of different strength grades under different substitution ratios, resulting in a strength influence coefficient curve. Figure 11 As the proportion of stone powder replacement increases, the overall compressive strength of concrete shows a decreasing trend. Regression analysis of the data yields the expression (I) for the strength influence coefficient under different stone powder replacement proportions: γ Lf = -3.16x 2 - 0.048x + 1 Equation (I) In the formula, x is the mass percentage (%) of stone powder replacing cement; This formula can provide a quantitative reference for the influence of different stone powder replacement ratios on concrete strength. Based on the strength influence coefficient expression (I), the strength influence coefficients of stone powder at replacement ratios of 10%, 15%, and 20% are obtained, and the results are shown in Table 13.

[0090] Table 13. Strength Influence Coefficient of Stone Powder at Different Doses

[0091] Considering the influence of stone powder particle size and chemical composition on strength, the strength influence coefficient values ​​for 10%, 15%, and 20% stone powder content were calculated at 95% confidence intervals, and envelope diagrams were plotted. Figure 12 The calculation results of the confidence interval of the intensity influence coefficient are shown in Table 14.

[0092] Table 14. Confidence intervals for the strength influence coefficient of stone powder under different dosages

[0093] 4.4 Determination of Upper and Lower Limits and Their Impact Based on the results in Table 14, the range of values ​​for the strength influence coefficient under stone powder replacement ratios of 10%, 15%, and 20% is shown in Table 15.

[0094] Table 15. Strength Influence Coefficient of Stone Powder at Different Dosages

[0095] Because the activation of stone powder requires a specific surface area of ​​350m², 2 Only when the stone powder is at least 1 kg or more and contains alkali or sulfate can it generate calcium silicate hydrate (CSH). Therefore, according to the results of the mortar test, under the premise of a certain substitution ratio, the influence of stone powder on the strength of cement-based materials mainly depends on the particle size or fineness of the stone powder. Therefore, whether it is calcareous or siliceous stone powder, the determination of the upper and lower limits of the 28-day strength influence coefficient mainly depends on the particle size of the stone powder. The fineness analysis of different stone powders can refer to the negative pressure sieving method in the standard "Cement Fineness Test Method - Sieve Analysis" (GB / T1345-2005). The stone powder sieve residue data is shown in Table 16.

[0096] Table 16. Percentage of mass remaining on sieves larger than 45μm (%)

[0097] The percentage of sieve residue for particles larger than 45μm obtained by negative pressure sieving can be used to determine the upper and lower limits. When it is less than 10%, the upper limit of the stone powder influence coefficient range calculated by the strength influence coefficient formula in this paper can be used. When it is between 10-20%, the calculated value of formula (I) can be directly used as the stone powder influence coefficient. When it is greater than 20%, the lower limit of the stone powder influence coefficient range obtained by formula can be used.

[0098] 4.5 Verification of the expression for the intensity influence coefficient Five types of stone powder from the same manufacturer but with different rock types and batches were randomly selected. Two common C30 and C50 mix proportions were randomly selected. To maintain the consistency of the selected mix proportions, concrete 28-day strength tests were conducted at random substitution ratios of 10%, 15%, and 20%. The calculated values ​​and experimental values ​​of formula (I) were compared and analyzed. The results are detailed in Table 17.

[0099] Table 17. Impact Coefficient Evaluation Analysis

[0100] As can be seen from the table, the ratio of the calculated value to the experimental value fluctuates around 1.0, and the calculated results are in good agreement with the experimental results. The mean and standard deviation of the ratio of the calculated value to the experimental value are 1.03 and 0.12, respectively, indicating that the strength influence coefficient expression obtained based on regression analysis has good predictive accuracy and applicability with the experimental values, and can be used to calculate the influence of 10%~20% stone powder content on concrete strength.

[0101] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for designing the mix proportion of manufactured sand concrete containing stone powder, characterized in that, It includes: (1) According to the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ55, the total mass of coarse and fine aggregates and the amount of cementitious materials in the reference concrete are calculated and determined by the absolute volume method, and the amount of cement, fly ash and mineral powder in the cementitious materials are determined respectively. (2) Using manufactured sand containing stone powder as fine aggregate, the stone powder content in the fine aggregate is determined by sieving, and stone powder is used to replace part of cement and / or fly ash and mineral powder in the mix proportion calculation to form a new type of cementitious system composed of cement, fly ash, mineral powder and stone powder in a specific proportion. The principles for stone powder substitution are as follows: Stone powder in manufactured sand can replace 10%-20% of the cement content; If there is any stone powder left over, the remaining stone powder will be used to replace fly ash and mineral powder. (3) Calculate the mortar strength of the novel cementitious system based on the strength influence coefficients of each component material, wherein the strength influence coefficient γ of the stone powder replacing cement is... Lf Calculate using the following formula: γ Lf = -3.16x 2 - 0.048x + 1 Equation (I) In the formula, x is the mass percentage (%) of stone powder replacing cement; (4) Calculate the required water-cement ratio based on the concrete mix strength: If the water-cement ratio meets the strength requirements, determine the corresponding water consumption; if not, readjust the amount of cementitious material and iterate until the water-cement ratio meets the strength requirements. (5) Finally determine the amount of each component in the unit volume of concrete.

2. The method for designing the mix proportion of manufactured sand concrete containing stone powder according to claim 1, characterized in that, The manufactured sand containing stone powder is derived from common diabase, basalt, dolomite, and limestone.

3. The mix design method for manufactured sand concrete containing stone powder according to claim 1, characterized in that, In step (2), when stone powder replaces cement in different proportions, the ratio of the strength of the resulting concrete to the strength of the reference concrete follows the following rule: When the proportion of stone powder replacing cement is 10% of the theoretical cement content, the strength ratio of the resulting concrete to the reference concrete strength is 89.0%-98.0%. When the proportion of stone powder replacing cement is 15% of the theoretical cement content, the strength of the resulting concrete is 84.5%-96.4% of the strength of the reference concrete. When the proportion of stone powder replacing cement is 20% of the theoretical cement content, the strength of the resulting concrete is 80.88%-89.82% of the strength of the reference concrete.

4. The mix design method for manufactured sand concrete containing stone powder according to claim 1, characterized in that, In step (3), to further incorporate the influence of stone powder particle size and chemical composition on concrete strength into the calculation system, the strength influence coefficient γ is calculated according to formula I. Lf Based on this, the range of values ​​for the strength influence coefficient corresponding to the 95% confidence interval of the stone powder replacement ratio is also introduced.

5. The mix design method for manufactured sand concrete containing stone powder according to claim 4, characterized in that, In step (3): When the stone powder replacement ratio is 10% of the theoretical cement content, the strength influence coefficient γ Lf The 95% confidence interval is 0.912–0.979; When the stone powder replacement ratio is 15% of the theoretical cement content, the strength influence coefficient γ Lf The 95% confidence interval is 0.848–0.964; When the stone powder replacement ratio is 20% of the theoretical cement content, the strength influence coefficient γ Lf The 95% confidence interval is 0.805-0.

866.

6. The mix design method for manufactured sand concrete containing stone powder according to claim 5, characterized in that, In determining the intensity influence coefficient γ Lf When determining the specific value, the following steps are also included: The stone powder was subjected to negative pressure sieving to determine the proportion of sieve residue of particles larger than 45μm. If the percentage of the sieve residue is less than 10%, then the upper limit of the corresponding confidence interval is taken as γ. Lf If the percentage of the sieve residue is 10%-20%, then the value calculated according to formula (I) is taken as γ. Lf If the percentage of the sieve residue is greater than 20%, then the lower limit of the corresponding confidence interval is taken as γ. Lf .

7. The mix design method for manufactured sand concrete containing stone powder according to claim 1, characterized in that, In step (2), the strength influence coefficient of the stone powder used to replace fly ash and mineral powder in equal amounts is the strength influence coefficient corresponding to the replaced fly ash and mineral powder. The value of the strength influence coefficient is determined in accordance with the provisions of the "Specification for Mix Proportion Design of Ordinary Concrete" JGJ 55.

8. A type of manufactured sand concrete containing stone powder, prepared according to the mix design method of any one of claims 1-7, characterized in that, Includes the following components: Cement, fly ash, mineral powder, water; Coarse aggregate, manufactured sand and fine aggregate containing stone powder; In this process, the stone powder in the manufactured sand serves as part of the cementitious material, and together with cement, fly ash, and mineral powder, it forms a composite cementitious system.

9. The stone powder-containing manufactured sand concrete according to claim 8, characterized in that, The stone powder is derived from powder with a particle size of less than 75μm produced during the production of manufactured sand from common diabase, basalt, dolomite, or limestone.

10. The stone powder-containing manufactured sand concrete according to claim 8, characterized in that, The 28-day compressive strength of the concrete shall not be less than 80% of the strength of the benchmark concrete without stone powder under the same conditions.

Citation Information

Patent Citations

  • Non-contact intelligent real-time detection method and device for content of machine-made sandstone powder

    CN112712519A

  • Proportioning and evaluation method of anti-crack roller compacted concrete based on stone powder modification

    CN119874296A

  • Design and construction integration-based early crack control method for outer wall of building

    CN120068239A

  • Concrete mix proportion design method based on machine-made sandstone powder as cementing material

    CN120089240A

  • Mix proportion design method of fiber shrinkage-compensating self-healing concrete

    CN120164553A

Cited By

  • Machine-made sand mortar performance regulation and control method based on hydration kinetics

    CN121494377A